Nilai-Nilai Pendidikan Karakter Dalam Tata Rias Wajah Punakawan Wayang Orang Sriwedari Surakarta - WIWEKO, Amung; , Dr. Sabar Narimo, M.M., M.Pd; , Drs. Djalal Fuadi, MM (2015)
The objectives of the research are: (1) to know make up characteristics of Punakawan Human Puppet of Sriwedari Surakarta; (2) to know symbolic meanings of Punakawan make up of Human Puppet of Sriwedari Surakarta; and (3) to know characters building values in Punakawan make up of Human Puppet of Sriwedari Surakarta. The design of the research is qualitative research in philosophy with hermeneutics approach. The material object of the research is philosophical concept in Punakawan make up and described in narrative form. The data are documents, interview result, and some photos of Punakawan make up. The data are collected through observation, interview, and documentation. The result shows that the characteristics of Semar make up describes Semar as wise, calm, and religious personality. the characteristics of Gareng make up describes Semar as talkless and honest personality. The characteristics of Semar make up describes Petruk as dynamic and caring personality. The characteristics of Bagong make up describes Bagong as stubborn, creative, an, and optimistic. Character building values in Semar make up are religious, peaceful, honesty, and nasionalism. Character building values in Gareng make up are honesty, peaceful, and nasionalism. Character building values in Petruk make up are communicative, peaceful, and optimistic, and Character building values in Semar make up are curiousity, dynamic and creative.